The legal rules of the European Union and the United States on artificial intelligence and human rights - Magdalena Butrymowicz (Deusto Journal of Human Rights)
In the contemporary era, artificial intelligence has become an integral component of our daily lives, permeating various facets of societal functioning with increasing prevalence. Given its pervasive presence in our lives, it is inevitable that AI exerts an influence on us, giving rise to the question of whether there is a nexus between AI and human rights. It is important to note that an algorithm created by an AI machine is devoid of feelings, emotions or prejudices. This may be indicative of a fundamental limitation of artificial intelligence as a tool in itself, constrained by the capabilities and capacities of technology, and thus incapable of perceiving and analyzing in the manner of the human mind. It is imperative that artificial intelligence is designed to be completely impartial and solely analyses the data entrusted to it for processing. Moreover, it should be capable of learning from its mistakes and being free of the emotions associated with human relationships. Conversely, it is as flawed as the human being behind its creation. In the contemporary era, there is an ongoing endeavor on the part of various nations to subjugate the domain of artificial intelligence to the provisions of a legal framework. There are three broad models for regulating AI: the first is based on regulations of the legal sector; the second is based on guidelines of inter-administrative organizations; and the third is based on legal solutions on other similar issues. The United States and the European Union have been at the vanguard of AI regulation, with each adopting different variants. The present publication sets out to compare EU and US legislation in the context of the matrix that served to create it, and to determine whether it regulates human rights. The issue of the rights of ethnic minorities is taken as a test case for this purpose.